Preparation and characterization of visible-light-driven europium doped mesoporous titania photocatalyst - 姚淑华 隋程程 石中亮 (Journal of rare earths, 2011)
pure and different content europium （Eu） doped mesoporous titania were prepared by template method using Eu（NO3）3·6H2O and Ti（OC4H9）4 as precursors and Pluronic P123 as template and characterized with X-ray diffraction （XRD）, N2 adsorption-desorption measure- ments, and ultraviolet-visible diffuse absorption spectra. Their photocatalytic activities were studied by photodegradation phenol in water un- der visible light irradiation. The results showed that Eu doping restrained the growth of grain size and extended the photoabsorption edge of mesoporous titania into the visible light region, which made Eu-doped mesoporous titania possess high photocatalytic activity under visible light. In the experiment condition, the photocatalytic activity of 0.2 mol.% Eu doped mesoporous titania was optimal of all the prepared samples.